The Fontan Adult Brompton clinical score and mortality risk - Montanaro, Claudia; Arvanitaki, Alexandra; Kerrigan, William; Kadani, Zehra; Barracano, Rosaria; Scognamiglio, Giancarlo; Kempny, Aleksander; Li, Wei; Brida, Margarita; McDonnell, Ella; Habibi, Hajar; Dimopoulos, Konstantinos; et al. (European heart journal, 2025)
Adults with congenital heart disease who underwent a Fontan palliation are at increased risk of premature death. This study aimed to identify a risk score based on widely available clinical variables at the first adult visit and facilitate personalized care. A single tertiary centre retrospective study included adults with a Fontan circulation during their first adults with congenital heart disease outpatient visit. Anatomic and periprocedural data, clinical, laboratory, and echocardiographic parameters at the first visit, and mortality or heart transplantation data were examined. A stepwise backward conditional approach was used to build a multivariate prognostic model, validated in an external retrospective cohort. Overall, 230 patients (49.6% female), the median age of 21.7 [interquartile range (IQR) 18.7-28.0] years, were included. Within 10.2 years of follow-up, 44 patients died and two received heart transplantation. A score including age at the first visit, history of atrial tachyarrhythmia, heart failure, New York Heart Association class, systolic blood pressure, and resting arterial oxygen saturation was derived, discriminating patients into low, intermediate, and high risk of death or transplantation [C-index: 0.71, 95% confidence interval (CI) 0.62-0.80]; discriminative ability was excellent (C-index 0.92, 95% CI 0.90-0.95) when externally validated in a cohort of 80 patients [41.2% female, median age 18.4 (IQR 17.3-24.8) years] with similar freedom from transplantation survival with the derivation cohort (log-rank P = .77). This novel, readily available, externally validated, clinical score identifies adult patients with a Fontan palliation at risk of mortality or transplantation and can be applied towards personalized care in this growing population with complex congenital heart disease.